Thugs and thieves: the differential etiology of violence - Savage, Joanne (Oxford University Press, 2016)
"It's often assumed that criminologists know a great deal about violent offenders, but in fact, there is little consensus about what distinguishes them from those who commit less serious crimes. There is even less agreement about whether violent offenders can be distinguished from chronic, nonviolent offenders at all. The challenging question remains: why do some individuals commit violent offenses while so many others restrict themselves to nonviolent ones? Thugs and Thieves argues that understanding the differential etiology of violence constitutes a fundamental chasm in the criminological literature. In the introductory chapters, the authors lay out the important theoretical and methodological deficiencies that have obstructed the production of a clear set of findings to answer this question. The authors then share a highly nuanced interpretation of child development research, focused on outlining important features of early life likely to be important in the etiology of serious physical aggression and violence. They also discuss criminal motivation and contextual factors in detail. Together, these lay the foundation for the selection of "good prospects" for predicting violent offending. Separate chapters are devoted to intelligence and executive function; academic achievement and other school factors; parental attachment; parental warmth and rejection; child abuse; poverty; communities; and substance abuse. Each chapter provides a comprehensive and systematic review of the existing evidence on the topic at hand through the "differential etiology" lens, to restructure what we already know from the empirical literature. As such, the book provides a new way forward for understanding this important issue and also serves as a platform for generating hypothesis tests, directing future research, and better designing anti-violence policy. Thugs and Thieves will be of interest to criminologists, psychologists, sociologists, students, policy makers, lawmakers, and readers interested in violence and aggression"--